EFFECT OF EARNING PER SHARE, CURRENT RATIO, DEBT TO l EQUITY RATIO IN PREDICTING FINANCIAL DISTRESS IN MINING COMPANIES - Ida Royani Silaban; Sri Ratnasari Harita; Wirda Lilia (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
This study aims to determine and test the effect of partial or simultaneous Earning Per Share, Current Ratio, and Debt to Equity Ratio on Financial Distress in Mining Companies Listed on the Indonesia Stock Exchange. The sampling technique uses purposive sampling technique, amounting to 14 companies with 4 years of observation. (four) years and data obtained from the financial statements of Mining Companies Listed on the Indonesia Stock Exchange at www.idx.co.id. The data analysis method used multiple linear regression analysis. Based on the research results, it is found that partially and simultaneously Earning Per Share, Current Ratio, and Debt to Equity Ratio have a significant effect on Financial Distress in Mining Companies Listed on the Indonesia Stock Exchange. The effect of Earning Per Share, Current Ratio, and Debt to Equity Ratio on Financial Distress in Mining Companies Listed on the Indonesia Stock Exchange is 53.9%.